Hubungan Tingkat Kecerdasan Emosional Terhadap Komunikasi Intrapersonal Islami Siswa Kelas IX MTS Al-Mustofawiyah - Najma Fauziyatul Mustaghfiroh; Nurul Farihatun Nisa (Al-Qolamuna: Journal Komunikasi dan Penyiaran Islam, 2025)
This study aims to determine the level of emotional intelligence and Islamic intrapersonal communication among ninth-grade students of MTs Al-Mustofawiyah, as well as to analyze the relationship between these two variables. The study employs a quantitative approach with a correlational research design. Data were collected through questionnaires, and observations to obtain a comprehensive picture of students’ emotional intelligence and Islamic intrapersonal communication practices. The data were then analyzed using descriptive quantitative techniques by calculating the minimum and maximum scores and mean values to identify the levels of both variables, and inferential analysis was conducted using Pearson correlation to examine the relationship between emotional intelligence and Islamic intrapersonal communication. The results indicate that students’ emotional intelligence has a mean score of 37.51, while Islamic intrapersonal communication has a mean score of 38.03, both of which fall within the moderate category. Meanwhile, the Pearson correlation analysis shows a correlation coefficient of r = 0.304 with a significance value of p = 0.076, indicating a positive relationship with a low level of correlation that is not statistically significant. These findings suggest that the development of Islamic intrapersonal communication does not entirely depend on emotional intelligence but is also influenced by other factors such as spiritual habituation, religious experiences, and a supportive educational environment. Therefore, this study provides additional insight into the role of emotional intelligence in the development of Islamic inner communication within the madrasah context. Abstrak Penelitian ini bertujuan untuk mengetahui tingkat kecerdasan emosional dan komunikasi intrapersonal Islami siswa kelas IX MTs Al-Mustofawiyah, serta menganalisis hubungan antara kedua variabel tersebut. Penelitian menggunakan pendekatan kuantitatif dengan desain korelasional. Data dikumpulkan melalui angket,  dan observasi untuk memperoleh gambaran yang menyeluruh mengenai kecerdasan emosional dan praktik komunikasi intrapersonal Islami siswa, kemudian dianalisis secara deskriptif kuantitatif dengan menghitung skor minimum, maksimum, dan nilai rata-rata untuk mengetahui tingkat kedua variabel, serta dianalisis secara inferensial menggunakan korelasi Pearson untuk menguji hubungan antara kecerdasan emosional dan komunikasi intrapersonal Islami. Hasil penelitian menunjukkan bahwa kecerdasan emosional siswa memiliki nilai rata-rata sebesar 37,51 dan komunikasi intrapersonal Islami sebesar 38,03 yang keduanya berada pada kategori sedang, sedangkan hasil analisis korelasi Pearson menunjukkan koefisien korelasi sebesar r = 0,304 dengan nilai signifikansi p = 0,076 yang mengindikasikan adanya hubungan positif dengan tingkat hubungan rendah dan tidak signifikan secara statistik. Temuan ini menunjukkan bahwa pengembangan komunikasi intrapersonal Islami tidak sepenuhnya bergantung pada kecerdasan emosional, melainkan juga dipengaruhi oleh faktor-faktor lain seperti pembiasaan spiritual, pengalaman religius, dan lingkungan pendidikan yang mendukung, sehingga penelitian ini memberikan wawasan tambahan mengenai peran kecerdasan emosional dalam pengembangan komunikasi batin Islami di lingkungan madrasah.